Event-Specific Cannabis Use and Use-Related Impairment: The Relationship to Campus Traditions - Buckner, Julia D. (J Stud Alcohol Drugs, 2015)
OBJECTIVE: Despite high rates of college cannabis use, little work has identified high-risk cannabis use events. For instance, Mardi Gras (MG) and St. Patrick’s Day (SPD) are characterized by more college drinking, yet it is unknown whether they are also related to greater cannabis use. Further, some campuses may have traditions that emphasize substance use during these events, whereas other campuses may not. Such campus differences may affect whether students use cannabis during specific events. The present study tested whether MG and SPD were related to more cannabis use at two campuses with different traditions regarding MG and SPD. Further, given that Campus A has specific traditions regarding MG whereas Campus B has specific traditions regarding SPD, cross-campus differences in event-specific use were examined. METHOD: Current cannabis-using undergraduates (N = 154) at two campuses completed an online survey of event-specific cannabis use and event-specific cannabis-related problems. RESULTS: Participants used more cannabis during MG and SPD than during a typical weekday, typical day on which the holiday fell, and a holiday unrelated to cannabis use (Presidents’ Day). Among those who engaged in event-specific use, MG and SPD cannabis use was greater than typical weekend use. Campus differences were observed. For example, Campus A reported more cannabis-related problems during MG than SPD, whereas Campus B reported more problems during SPD than MG. CONCLUSIONS: Specific holidays were associated with more cannabis use and use-related problems. Observed between-campus differences indicate that campus traditions may affect event-specific cannabis use and use-related problems.